Conformal metal crack detection sensor based on flexible graphene film antenna. Issue 7 (30th March 2022) - Tong, Cong; Song, Rongguo; Guan, Huijuan; Yang, Yingping; He, Daping
Abstract: Crack detection of metal structures is an important procedure to ensure the safe operation of metal structures. In this work, a metal crack sensor based on a highly conductive flexible graphene film is proposed. The sensor is designed based on conformal microstrip antenna composed of a flexible graphene film radiation patch and a flexible dielectric substrate. The prepared sensor exhibited a detection sensitivity of 36.82 MHz/mm demonstrated by both experimental and simulation results. Moreover, benefiting from the flexible nature of the graphene film, the proposed sensor shows good conformality which makes up the shortcoming of the traditional rigid crack detection device.